Pembinaan Etika Akademik Mahasiswa Generasi Z dalam Membentuk Kompetensi Kepribadian Calon Pendidik - Nuristiqamah Awaliyahputri B.; Miswar Miswar; Abdul Aji Ibrahim Lubis (Universitas Pendidikan Mandalika, 2023)
This study aims to describe the form of academic ethics coaching for Generation Z students in shaping the personality competence of prospective educators at UIN Sumatera Utara Medan. The research method used was descriptive with a qualitative approach. The informants in this study were leaders (Vice Dean III and Head of Study Program), lecturers, and students. The research instruments used were observation sheets, interview instruments, and documentation. The data analysis technique started with data collection, reduction, display, and verification. The results of this study indicated that the form of academic ethics coaching for Generation Z students in shaping the personality competence of educators could be done through 1) Introduction to Academic and Student Culture (PBAK) activities, 2) Lecture process, 3) Delivery of academic information orally and in writing; 4) Guidance to Academic Advisor (PA) Lecturers; 5) Providing sanctions following the level of violation, namely mild sanctions, moderate sanctions, and severe sanctions.